1999
DOI: 10.1902/jop.1999.70.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Tubercles, Palatal Tori, and Mandibular Tori: Prevalence and Anatomical Features in a U.S. Population

Abstract: The prevalence and features of 3 types of exostoses commonly encountered during periodontal surgery were studied in a sample of 328 modern American skulls drawn from the collection at the American Museum of Natural History. Measurements were made of the height, width, and breadth of exostoses. The relationship to teeth or other skeletal structures was also recorded. Palatal tubercles were observed in 56% of all skulls (69% of all dentate skulls), with higher prevalences among males and African-Americans. Palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
117
5
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(147 citation statements)
references
References 0 publications
17
117
5
8
Order By: Relevance
“…However, it should be noticed that intraoral toris were only observed in 15% of all subjects (Table 1). Sonnier et al 3 observed that palatal alveolar exostoses and mandibular tori can be found more often in young male dentate subjects (suggestive of alveolar bone origin). In contrast, the collective results from published case reports and the findings of the present paper (Table 1) indicate that 90% of the 20 subjects, who presented BBE after FGG, are females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noticed that intraoral toris were only observed in 15% of all subjects (Table 1). Sonnier et al 3 observed that palatal alveolar exostoses and mandibular tori can be found more often in young male dentate subjects (suggestive of alveolar bone origin). In contrast, the collective results from published case reports and the findings of the present paper (Table 1) indicate that 90% of the 20 subjects, who presented BBE after FGG, are females.…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular tori were observed in more than a quarter of modern dry skulls and palatal alveolar exostoses in more than a half. 3 Both BE species may be found more usually in young male dentate subjects, probably from alveolar bone origin. 3 Multiple exostoses are found somewhat less usually than mandibular tori or palatal alveolar exostoses on the maxillary buccal surface below the mucobuccal fold in the molar region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TP etiology remains unclear 6,7 . Efforts to link its occurrence to third molar agenesia 8 , bone density 9 and elongation of styloid process 10 have been made, but these relationships remain a source of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to link its occurrence to third molar agenesia 8 , bone density 9 and elongation of styloid process 10 have been made, but these relationships remain a source of debate. Nowadays, the most widely accepted theory is that TP represents genetic traits 6,7,[11][12][13][14][15] , but it has not always been possible to show the autosomal dominant nature of these structures 15 . Others 16,17 have considered that the development of TP results from an interplay of genetic and environmental factors, especially those related to occlusal stress 2 .…”
Section: Discussionmentioning
confidence: 99%